The Psychosomatic Effects of Childhood Trauma: Insights from Adult Survivors - Saadati, Nadereh; Kiliçaslan, Fethiye; Salami, Mutiu Olagoke (Journal of Personality and Psychosomatic Research (JPPR), 2024)
This study aims to explore the psychosomatic effects of childhood trauma from the perspectives of adult survivors. It seeks to understand the multifaceted impact of early adverse experiences on individuals’ emotional, physical, and psychological well-being in adulthood. A qualitative research design was employed, utilizing semi-structured interviews with 30 adult survivors of childhood trauma. Participants were selected through purposive and snowball sampling to ensure a diverse representation of experiences. Data were analyzed using thematic analysis to identify patterns, themes, and insights related to the psychosomatic effects of childhood trauma. Theoretical saturation was achieved, confirming the comprehensiveness of the data collected. The study identified five main themes encapsulating the psychosomatic effects of childhood trauma: Emotional Responses, Physical Symptoms, Coping Mechanisms, Interpersonal Effects, and Psychological Well-being. Each theme comprised several categories, with key findings illustrating a wide range of emotional turmoil, somatic manifestations, varied coping strategies, significant interpersonal challenges, and profound impacts on psychological well-being. Emotional Responses highlighted the depth of survivors’ feelings, from anger and sadness to hope and resilience. Physical Symptoms underscored the bodily toll of trauma, including sleep disturbances and chronic pain. Coping Mechanisms revealed both maladaptive and adaptive strategies employed by survivors. Interpersonal Effects delved into the impact on relationships and social interactions. Psychological Well-being addressed the enduring psychological scars and the potential for growth. The study provides comprehensive insights into the complex psychosomatic effects of childhood trauma on adult survivors. It underscores the need for holistic and tailored interventions that address the emotional, physical, and psychological impacts of such experiences. Recognizing the nuanced coping strategies and interpersonal challenges faced by survivors is crucial for developing effective support systems.